Women's Political Leadership and Adult Health: Evidence from Rural and Urban China. (March 2021) - Xu, Hongwei; Luke, Nancy; Short, Susan E.
This study examined the role of women's political leadership at the community level in China, a context that has experienced recent political and socioeconomic change and has a distinctive rural–urban divide. Drawing on longitudinal data from the China Family Panel Studies (N range = 40, 918–52, 406 person-year observations), we found that female community directors outnumbered male directors in urban China but were much less common in rural areas. Female community directors had higher levels of human capital regardless of rural or urban location. Residents living in female-directed communities reported better mental health but not physical health or life satisfaction compared to those living in male-directed communities, and this association was most robust among rural women. For rural women, the mental health benefit of living in female-directed communities was partially explained by reduced personal experience of gender discrimination, suggesting that female leadership fosters ideational change toward women that lowers discriminatory behaviors among constituents.